The Impact of Technology Innovation Output on Firm Value of Technology Innovation SMEs in China - Liu, Zichang; Nik Azman, Nik Hadiyan Binti (Business Management and Strategy, 2025)
With the advent of the big data era, technological innovation has become the driving force behind the expansion of technology innovation SMEs. Where feasible, enterprises must rely on the development of technology innovation SMEs as soon as possible to strengthen their national power and achieve sustainable development. Understanding the relationship between technological innovation output and firm value is crucial for developing R&D budgets and guiding some strategic decisions of top managers in firms. This article research the impact of technological innovation output on the firm value of technology innovation SMEs, this study is based on the data from 2019 to 2023 of the listed enterprises in China's Science and Technology Innovation Board (STAR MARKET), and regression analyses are technological innovation outputs (Intangible assets and Patent) and firm value. It was found that technological innovation output has a negative effect on firm value. This effect is equally applicable to companies of different age of establishment, especially for companies with a shorter period of establishment; the negative effect is more prominent.